2012
DOI: 10.1177/1531003512454581
|View full text |Cite
|
Sign up to set email alerts
|

Thromboprophylaxis Practices Following Varicose Veins Surgery

Abstract: Thromboprophylaxis practices following varicose veins procedures vary among vascular surgeons in Greece. This reflects the uncertainty regarding the exact incidence of thromboembolic events in the existing literature as well as the absence of specific guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…There is a lot of variation in practice with regard to routine thromboprophylaxis. Nikopoulos et al surveyed Greek vascular surgeons in 2012 10 and found that 58% give thromboprophylaxis routinely after endovenous procedures. An older survey from 1995 of the Vascular Surgical Society of Great Britain and Ireland 21 showed that only 12% gave routine prophylaxis after open varicose vein surgery.…”
Section: Thromboprophylaxis -Practice and Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a lot of variation in practice with regard to routine thromboprophylaxis. Nikopoulos et al surveyed Greek vascular surgeons in 2012 10 and found that 58% give thromboprophylaxis routinely after endovenous procedures. An older survey from 1995 of the Vascular Surgical Society of Great Britain and Ireland 21 showed that only 12% gave routine prophylaxis after open varicose vein surgery.…”
Section: Thromboprophylaxis -Practice and Factorsmentioning
confidence: 99%
“…A recent survey of vascular surgeons in Greece showed that 52% use routine thromboprophylaxis for open varicose surgery and 58% for endovenous, suggesting a lack of consensus. 10 Given this uncertainty, the aim of this study was to assess thromboprophylaxis practice for varicose vein procedures among vascular surgeons in Ireland.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be pointed out that there were no reports of use of other types of heparin or fondaparinux. 9 …”
Section: Discussionmentioning
confidence: 99%
“…15 There remains widespread disparity on the administration and regimen of thromboprophylaxis following varicose vein surgery. 17 Strategies may include no pharmacological thromboprophylaxis, targeted therapy, or routine single-dose or extended-duration thromboprophylaxis. This variability may reflect clinical uncertainty regarding best practice.…”
Section: Thromboprophylaxis Following Superficial Venous Interventionmentioning
confidence: 99%